Integrasi Pembiasaan Religius dalam Pencapaian Nilai Agama dan Moral Anak Usia Dini: Studi di PAUD Adz-Dzikra - Rahmat, Mamat; Rohmatin, Alfa; Ihsan Ihsan; Siti Rafilda Maldah; Andriawan Andriawan; Dewi Nurmuslihat; N Alfiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the religious habituation strategies implemented at PAUD Adz-Dzikra in developing religious and moral values among children aged 5–6 years, as well as to analyze the behavioral changes resulting from these practices. Using a descriptive qualitative approach, the research involved 50 children and 4 teachers. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the habituation activities—such as Iqra reading practice, short surah memorization, Dhuha prayer, and the Friday Cleaning program—significantly contributed to the development of children’s religious and moral values. Children not only recognized basic religious teachings but were also able to apply them in real actions, including reading hijaiyah letters, performing simple worship, demonstrating politeness, honesty, helpfulness, and maintaining personal and environmental cleanliness. The religious habituation strategies applied at PAUD Adz-Dzikra proved effective in internalizing religious and moral values in accordance with the indicators of the Early Childhood Development Achievement Standards (STPPA) stated in the Ministry of Education and Culture Regulation No. 137 of 2014. This study confirms that consistent habituation is a fundamental approach to developing religious character in early childhood.